Information-Seeking Behavior of Research Scholars: A Developing University’s Perspective - Dr. Muhammad Zahid Raza; Ali, Dr. Asif (IJoLIS, 2025)
Objectives: This study has been designed to determine the information-seeking behavior (ISB) of research scholars at the University of Sargodha, Pakistan. ISB was assessed by exposing purposes of information, preferred information sources, monitoring new publications, managing print information, managing electronic sources, sifting information sources, selecting information resources, and selecting the preferred format of scholars. Methodology: A structured questionnaire-based survey using a quantitative research approach was adopted to achieve the study’s objectives by collecting data from all the research scholars of the University of Sargodha, Pakistan. Findings: This study concludes that a majority of research scholars use information for synopsis preparation, followed by data collection, data analysis, open defense, and article publishing in their ISB. A majority of research scholars preferred the Internet for information seeking, followed by books, journals, and electronic databases. A majority of scholars monitor new publications in their research by reading abstracts and indexes followed by tables of contents. Scholars categorized their information sources by subject and library name. Most of the scholars manage the information sources in separate folders, followed by Google Drive, hard drives, and USBs. The majority of the scholars read the introduction and conclusion, followed by the abstract, index reading, etc. Scholars mostly used electronic format, followed by print format. Significance: The present study was conducted to invigorate the scholarly literature in the present digital era context. This study will provide us with a comprehensive true picture regarding the ISB of research scholars of developing university that will be supportive to plan bibliographic teaching, information literacy programs, researchers’ information behavior for policymakers, educationists, researchers, librarians, faculty, and higher education departments. The results have practical and theoretical ramifications for academic and research institutions, federal and provincial higher education commissioners, and policy organizations.